Open-source automated centrifugal pump test rig. (October 2020) - Semenzin, Clayton S.; Mapley, Martin; Wu, Eric; Pauls, Jo P.; Simpson, Benjamin; Gregory, Shaun D.; Tansley, Geoff
Graphical abstract: Abstract: Design methods for large industrial pumps are well developed, but they cannot be relied upon when designing specialised miniature pumps, due to scaling issues. Therefore, the design and development phase of small pumps demand numerous experimental tests to ensure a viable prototype. Of initial interest is hydraulic design in the form of pump performance and efficiency curves. This project aimed to produce an automated test rig capable of generating both the performance (P-Q – pressure vs. flow rate) and efficiency curves that are reliable and repeatable. The apparatus is largely customizable and suitable for a range of smaller pump sizes. The pump impeller and volute were 3D printed, allowing for design flexibility and rapid prototyping and testing. The test loop was automated which allowed the flow rate to be incremented from 0 L/min to the maximum flow rate. At each step the pressure, flow rate, voltage and current were recorded to generate the P – Q and efficiency curves. Repeatability results showed low variations of ±3 mmHg (400 Pa) in pressure and ± 2% in hydraulic efficiency. The given setup can be used to compare and evaluate the hydraulic performance of various pump designs.